2018
DOI: 10.1371/journal.pntd.0006651
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of population dynamics of Bulinus globosus: Effects of environmental temperature on production of Schistosoma haematobium cercariae

Abstract: BackgroundTemperature is an important factor that influences the biology and ecology of intermediate host (IH) snails and the schistosome parasites they transmit. Although temperature shifts due to climate change has been predicted to affect the life history traits of IH snails and parasite production, the mechanisms of how this may affect parasite abundance and disease risks are still not clear.Materials and methodsUsing data from laboratory and field experiments, we developed a deterministic compartmental si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Our findings show that the Madeya community relies on surface water (unprotected dug wells, rivers and dams) as the main source of water for domestic use. This implies that the risk of contracting schistosomiasis infection from exposure to cercariae infested waters was high [33,34]. Previous studies in the same area reported high prevalence of schistosomiasis among school-going children [11,12].…”
Section: Discussionmentioning
confidence: 95%
“…Our findings show that the Madeya community relies on surface water (unprotected dug wells, rivers and dams) as the main source of water for domestic use. This implies that the risk of contracting schistosomiasis infection from exposure to cercariae infested waters was high [33,34]. Previous studies in the same area reported high prevalence of schistosomiasis among school-going children [11,12].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, medium sized snails are best suited to withstand desiccation on the soil surface because of a more favourable aperture size/weight ratio (Hira, 1968;Diaw et al, 1988). Secondly, humid soils offer better survival chances (Ohlweiler & Kawano, 2001;Kalinda et al, 2018a) although aerobic conditions remain a prerequisite (Chu et al, 1967a;Coles, 1969;Betterton, 1984;Ebele & Smith, 1990;Thomas & Daldorph, 1991). This explains why survival rates are lower in wet mud and places exposed to sunlight (Chu et al, 1967c;Hira, 1968;Van Aardt & Steytler, 2007) and why they increase when IH snails bury in moist mud (Chu et al, 1967a;Kalinda et al, 2018b).…”
Section: The Effect Of Climatic Factors and Waterbody Characteristics On Snail Distributionsmentioning
confidence: 99%
“…In contrast, Kalinda and co-workers [129] used data from laboratory and field experiments to develop a deterministic compartment simulation model for the life cycle of B. globosus. Their model generated fecundity of snail and survival rates similar to those in the laboratory.…”
Section: Role Of Mathematical Modelling In Disease Epidemiological Stmentioning
confidence: 99%
“…It was also shown that there is decrease in number of both the snails and cercariae due to an increase in the environmental temperatures, with maximum reduction in abundance of snails by 14% and 27% and decrease in maximum cercariae by 8% and 17% when the temperatures were increased by 1 • C and 2 • C, respectively. Their findings suggested that a rise in future temperature due to climate change may alter the abundance of B. globosus and influence the prevalence of schistosomiasis [129].…”
Section: Role Of Mathematical Modelling In Disease Epidemiological Stmentioning
confidence: 99%